Effective Tax Rates: Firm Size, Leverage and Return on Assets - Widati, Sindik; Asiah, Neng; Kamela, Hurian; Hidayat, Tanti Amalia (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Effective Tax Rate (ETR) assesses a company's proficiency in managing its tax burden by comparing tax expenses to total net income. A lower ETR percentage indicates better tax effectiveness. Companies utilize the ETR as a benchmark for shaping their tax policies. It serves as a tool for gauging how well a company handles its tax system. This study seeks empirical evidence on the impact of firm size, leverage, and return on assets on effective tax rates. The independent variables include firm size, debt level, and return on assets, while the dependent variable is the effective tax rate. The research focuses on food and beverages sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The sample comprises 34 companies selected through purposive sampling. The analysis employs multiple linear regression, revealing that firm size and return on assets do not influence effective tax rates, whereas leverage significantly affects the effective tax rate